Heavy oil-based high-capacity capacitor carbon material, preparation method thereof and supercapacitor
By using a composite of heavy oil, oxygen-containing catalyst and activator, the problem of ineffective utilization of super-heavy components in heavy oil is solved, and the yield and electrochemical performance of capacitive carbon materials are significantly improved, and the performance of supercapacitors is improved.
Patent Information
- Application Number
- CN202311370065.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-04-22
AI Technical Summary
The prior art is difficult to effectively utilize the superheavy components in heavy oil, which makes it impossible to be effectively utilized. The pores of the produced activated carbon material are concentrated in micropores, which is not conducive to the transmission and storage of electrolyte ions and affects the capacity and cycle life of the supercapacitor.
A composite of heavy oil, oxygen-containing catalyst and activator is used for molding and processing, and capacitive carbon materials with high specific surface area and rich micro-mesoporous are prepared through activation reaction, pickling, water washing and ball grinding and other steps.
Effectively eliminate the sticky wall phenomenon during the activation process, reduce the alkali-carbon ratio, significantly improve the yield of capacitive carbon products, obtain capacitive carbon materials with high specific surface area and rich pore structure, and improve the capacity and cycle stability of supercapacitors.
Smart Images

Figure CN119864243A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of material science and electrochemical technology, and specifically relates to a heavy oil-based high-capacity capacitor carbon material and a preparation method thereof. Background Art
[0002] Heavy oil is referred to as heavy oil, which is the heavy component in conventional crude oil, such as residual oil and asphalt, or refers to natural heavy crude oil, such as oil sands. In the process of petroleum processing, the heavy components obtained by atmospheric and vacuum distillation of crude oil or the heavy components produced in secondary processing such as catalytic cracking and delayed coking can be called heavy oil.
[0003] In the period when the development of oil refining technology was relatively backward, heavy oil became a well-utilized tail oil, generally used as fuel oil for heating furnace combustion and heat release, or as fuel for large oil-fired units. This utilization method has low thermal efficiency, is very likely to cause equipment clogging and corrosion, and reduce service life. At the same time, a large amount of harmful gases emitted seriously pollute the environment. In the past 10 years, with the rapid development of the oil refining industry, people have acquired the ability to process and utilize heavy oil, such as heavy oil catalytic cracking, hydrocracking, and residual oil hydrogenation processes developed in recent years, which have achieved initial results. However, despite the effective processing and utilization of heavy oil, there are still some ultra-heavy components that cannot be used as residual products of processing, such as deoiled asphalt, petroleum coke, etc. This part can often only be used as road construction and building materials, with low added value, resulting in waste of resources. Therefore, the rational and effective utilization of this part of heavy oil resources remains the focus of the next work.
[0004] Supercapacitors, also known as electrochemical capacitors, are energy storage devices between capacitors and batteries. They are a new type of green and pollution-free energy storage device with the characteristics of fast charging and discharging speed, long service life, high power density, and high energy conversion efficiency. Therefore, supercapacitors have great application prospects in many fields. Supercapacitors are mainly composed of electrode materials, diaphragms, electrolytes, current collectors and other components. Among them, electrode materials are the key to determining the electrochemical properties of supercapacitors. Supercapacitor electrodes require high-performance activated carbon with developed micropores, large specific surface area, and large pore volume. The pores of activated carbon produced by existing methods are mainly concentrated in micropore distribution, which is not conducive to the transmission and storage of electrolyte ions, and seriously affects the capacity and cycle life of supercapacitors.
[0005] In summary, using heavy oil as a precursor to directly synthesize carbon materials for supercapacitors can not only solve the increasingly severe energy shortage problem, but also effectively develop the application path of heavy oil-based high value-added products. Therefore, developing new process technologies with short process routes, low costs, high yields and good performance is the primary task for realizing the commercial application of heavy oil-based electrode materials. Summary of the invention
[0006] In view of the current problems, the purpose of the present invention is to provide a capacitor carbon material and a preparation method thereof. The preparation method uses heavy oil as raw material and can achieve large-scale preparation of high-capacity capacitor carbon materials with high specific surface area and rich micro-mesopores.
[0007] To achieve the above object, the present invention provides a method for preparing a heavy oil-based high-capacitance capacitor carbon material, wherein the method comprises:
[0008] (1) mixing heavy oil, an oxygen-containing catalyst, and an activator to obtain a composite, and subjecting the composite to a molding process; wherein the mass ratio of the heavy oil to the oxygen-containing catalyst is 1:1-1:10, and the mass ratio of the heavy oil to the activator is 1:0.2-1:5;
[0009] (2) activating the formed composite;
[0010] (3) The activated product is acid-washed, washed with water until neutral, dried, and ball-milled to obtain the capacitor carbon material.
[0011] In the above preparation method, preferably, the heavy oil includes one or a combination of two or more of petroleum coke, ethylene tar, heavy diesel, petroleum asphalt, vacuum residue oil, vacuum wax oil, atmospheric residue oil, atmospheric wax oil, etc.
[0012] In the above preparation method, preferably, the oxygen-containing catalyst includes one or a combination of two or more of magnesium oxide, copper oxide, calcium oxide, aluminum oxide, magnesium sulfate, copper sulfate, iron sulfate, zinc sulfate, calcium sulfate, sodium carbonate, potassium carbonate, magnesium carbonate, copper carbonate, calcium carbonate, and zinc carbonate.
[0013] In the above preparation method, preferably, the activator includes one or a combination of two or more of potassium hydroxide, sodium hydroxide, zinc chloride and phosphoric acid.
[0014] In the above preparation method, preferably, the mass ratio of the heavy oil to the oxygen-containing catalyst is 1:1-1:5.
[0015] In the above preparation method, preferably, the mass ratio of the heavy oil to the activator is 1:0.5-1:5, more preferably 1:0.5-1:2.
[0016] In the above preparation method, preferably, the molding process is performed by extrusion molding, more preferably, the pressure of the extrusion molding is 0.5-20 MPa, more preferably 0.5-10 MPa.
[0017] In the above preparation method, preferably, the activation reaction is carried out under protective gas conditions; more preferably, the protective gas includes one or a combination of two or more of nitrogen, helium and argon.
[0018] In the above preparation method, preferably, the gas velocity of the protective gas is 0.01-10 L·min -1 , more preferably 0.01-5 L·min -1 .
[0019] In the above preparation method, preferably, the temperature of the activation reaction is 700-1000° C. (more preferably 700-900° C.), and the reaction time is 0.5-3 h (more preferably 1-2 h).
[0020] In the above preparation method, preferably, the heating rate during the activation reaction is 5-10°C·min -1 , more preferably 5-8℃·min -1 .
[0021] In the above preparation method, preferably, the pickling solution used in the pickling is one or a combination of two or more of dilute hydrochloric acid and dilute sulfuric acid.
[0022] In the above preparation method, preferably, the particle size of the product obtained by ball milling is in the range of 0.1-50 μm, more preferably 10-30 μm.
[0023] In the above preparation method, preferably, the ball milling time is 0.5-10h.
[0024] According to a specific embodiment of the present invention, preferably, the above preparation method comprises the following specific steps:
[0025] (1) heavy oil, oxygen-containing catalyst, and activator are uniformly mixed according to a mass ratio to obtain a composite, and the composite is subjected to an extrusion molding process;
[0026] (2) placing the formed composite in an activation furnace reactor to perform an activation reaction under high temperature conditions and an inert atmosphere;
[0027] (3) The activated product is acid-washed, washed with water until neutral, and then dried, and crushed by ball milling to obtain a capacitor carbon material.
[0028] The present invention also provides a capacitor carbon material prepared by adopting the preparation method of heavy oil-based high-capacitance capacitor carbon material.
[0029] According to a specific embodiment of the present invention, preferably, the specific surface area of the capacitor carbon material is 1000-3000m 2 ·g -1 , pore volume is 0.05-5cm3 ·g -1 , the pore size distribution is 0.5-100nm.
[0030] The present invention also provides the use of the above capacitor carbon material as an electrode material for a supercapacitor.
[0031] The present invention also provides a supercapacitor, wherein the electrode material of the supercapacitor is made of the above-mentioned capacitor carbon material.
[0032] The present invention has found that in the process of preparing capacitor carbon materials using heavy oil as raw material, wall sticking phenomenon is prone to occur, and the main reason for the wall sticking phenomenon is that the proportion of activator is high, that is, the alkali carbon ratio is high, resulting in serious loss of intermediate melt, low activation efficiency, and easy adhesion after contact with the reactor wall, resulting in the inability of capacitor carbon to be produced continuously. The preparation method of the present invention adopts catalytic activation process technology, and the catalyst in the process is a catalyst rich in oxygen elements. The oxygen-containing catalyst can significantly promote the cracking and dehydrogenation of condensed aromatic hydrocarbons in medium and heavy oils. Under the synergistic effect of the activation of the activator and the catalytic cracking of the catalyst, the carbon fixation efficiency is significantly improved, and then the yield of capacitor carbon is significantly improved. In addition, under the synergistic effect of catalytic cracking and activation, the proportion of the activator can be significantly reduced, thereby reducing the alkali carbon ratio, which can effectively eliminate the wall sticking problem in the activation process.
[0033] The capacitor carbon material of the present invention exhibits good electrochemical properties in both aqueous and organic electrolyte systems, indicating that it has good compatibility with different types of electrolytes.
[0034] Compared with the prior art, the advantages of the present invention are that the wall sticking phenomenon in the activation process can be effectively eliminated through a simple method, the alkali-carbon ratio can be reduced, the yield of the capacitor carbon product can be greatly improved, and a capacitor carbon material with a high specific surface area and rich pore structure can be obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is a scanning electron microscope image of the capacitive carbon material prepared in Example 1 of the present invention.
[0036] Figure 2 This is a transmission electron microscope image of the capacitive carbon material prepared in Example 1 of the present invention.
[0037] Figure 3 This is the nitrogen adsorption / desorption curve of the capacitor carbon material prepared in Example 1 of the present invention.
[0038] Figure 4 This is the pore distribution curve of the capacitor carbon material prepared in Example 1 of the present invention.
[0039] Figure 5This is the X-ray powder diffraction spectrum of the capacitor carbon material prepared in Example 1 of the present invention.
[0040] Figure 6 This is a rate performance diagram of the capacitive carbon electrode prepared in Example 1 of the present invention.
[0041] Figure 7 This is the charge and discharge curve of the capacitor carbon electrode prepared in Example 1 of the present invention.
[0042] Figure 8 This is the cyclic voltammetry curve of the capacitive carbon electrode prepared in Example 2 of the present invention.
[0043] Fig. 9 This is the pore distribution curve of the capacitor carbon material prepared in Example 3 of the present invention.
[0044] Fig.10 This is the X-ray powder diffraction spectrum of the capacitor carbon material prepared in Example 3 of the present invention.
[0045] Fig.11 This is a cycle performance diagram of the capacitor carbon electrode prepared in Example 3 of the present invention.
[0046] Fig.12 This is the pore distribution curve of the capacitor carbon material prepared in Example 4 of the present invention.
[0047] Fig.13 This is the X-ray powder diffraction spectrum of the capacitor carbon material prepared in Example 4 of the present invention.
[0048] Fig.14 This is the cyclic voltammetry curve of the capacitive carbon electrode prepared in Example 4 of the present invention.
[0049] Fig.15 This is the pore distribution curve of the capacitor carbon material prepared in Example 5 of the present invention.
[0050] Fig.16 This is the X-ray powder diffraction spectrum of the capacitor carbon material prepared in Example 5 of the present invention.
[0051] Fig.17 This is the cyclic voltammetry curve of the capacitive carbon electrode prepared in Example 5 of the present invention. DETAILED DESCRIPTION
[0052] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0053] Example 1
[0054] This embodiment provides a method for preparing a heavy oil-based capacitor carbon material, wherein the preparation method comprises the following specific steps:
[0055] (1) crushing petroleum asphalt and passing it through a 200-mesh sieve to obtain petroleum asphalt powder;
[0056] (2) mixing the petroleum asphalt powder, magnesium oxide and potassium hydroxide obtained in step (1) in a mass ratio of 1:1:1, placing the composite in a high-speed stirrer and rapidly stirring for 20 minutes to obtain a uniformly mixed composite;
[0057] (3) subjecting the composite to an extrusion molding process at an extrusion pressure of 10 MPa;
[0058] (4) The formed composite was placed in an activation furnace reactor, argon was introduced, and the heating rate was 5°C min -1 , reaction temperature 850℃, reaction time 1h;
[0059] (5) After the reaction product is cooled to room temperature, the reaction product is taken out, purified with 15 wt % dilute hydrochloric acid and washed with deionized water, dried in an oven at 120° C. for 12 h, and ball-milled for 2 h to obtain a capacitor carbon powder material.
[0060] When the reaction product is taken out in step (5), there is no mutual adhesion between the product and the reactor wall, and the mutual independence of the product and the reactor wall is relatively intact. The product is very easy to take out, indicating that there is no wall adhesion during the preparation process of capacitor carbon, further indicating that the method of the present invention can effectively eliminate the wall adhesion phenomenon during the preparation process of capacitor carbon.
[0061] This embodiment also provides a method for preparing a capacitor carbon electrode using the above capacitor carbon powder material, which comprises:
[0062] The capacitor carbon material, binder (LA133) and conductive additive (acetylene black) were dispersed in deionized water at a mass ratio of 8:1:1, and then the mixture was homogenized in a homogenizer. After homogenization for 5 hours, a capacitor carbon slurry was obtained.
[0063] The capacitor carbon slurry was evenly coated on a nickel foam with a thickness of 1 mm and a diameter of 12 mm, and placed in a constant temperature drying oven at 120° C. to remove the solvent, thereby obtaining a dry capacitor carbon electrode.
[0064] Performance Test:
[0065] The concentration was 6 mol·L -1 The KOH solution and the concentration are 1 mol·L -1TEABF4 solution was used as aqueous and organic electrolytes, and glass fiber filter membrane (GF / D, Whatman, GE) was used as the diaphragm. Electrode sheets of the same mass were assembled into supercapacitors with aqueous and organic electrolyte systems, and subsequent capacitance performance evaluation was carried out.
[0066] Figure 1 This is a scanning electron microscope image of the capacitor carbon prepared in Example 1 of the present invention. The capacitor carbon material presents a lamellar porous structure and has good structural integrity.
[0067] Figure 2 This is the transmission electron microscope image of the capacitor carbon, where a rich pore structure can be observed.
[0068] Figure 3 This is the nitrogen adsorption / desorption curve of the capacitor carbon material. With the increase of relative pressure, the adsorption amount of the capacitor carbon material shows a slow upward trend, and the isotherm shape begins to have characteristics tending to type IV, indicating that there are a certain amount of mesopores inside it.
[0069] Figure 4 is the pore distribution curve of the capacitor carbon material. The specific surface area of the capacitor carbon material is 1616m 2 ·g -1 , pore volume is 1.01cm 3 ·g -1 The pores of capacitive carbon are composed of micropores and mesopores, and the pore size distribution is concentrated between 0.5-100nm.
[0070] Figure 5 This is the X-ray powder diffraction spectrum of the capacitor carbon material. The material has a wide and weak 002 peak, indicating that the material contains more thin layer structures. In addition, the peak intensity of the material in the low-angle diffraction area is high, which also shows that it has a rich pore structure.
[0071] Figure 6 The rate performance diagram of the capacitive carbon electrode in the aqueous electrolyte system is shown in Figure 1. -1 At a current density of 230 F·g -1 , and at 100A·g -1 , the capacity can still reach 193F·g -1 , reflecting the excellent rate performance.
[0072] Figure 7 The charge-discharge curve of the capacitive carbon electrode in the aqueous electrolyte system shows a high degree of symmetry, indicating that the double-layer energy storage process on the electrode surface is highly reversible. -1 At a current density of 2.5 Å, the capacity of the capacitive carbon electrode in an organic electrolyte system is as high as 215 F·g -1 .
[0073] The above results show that the capacitive carbon electrode material exhibits good electrochemical properties in both aqueous and organic electrolyte systems, indicating that it has good compatibility with different types of electrolytes.
[0074] Example 2
[0075] This embodiment provides a method for preparing heavy oil-based capacitor carbon, wherein the preparation method comprises the following specific steps:
[0076] (1) crushing petroleum asphalt and passing it through a 200-mesh sieve to obtain petroleum asphalt powder;
[0077] (2) mixing the petroleum asphalt powder, magnesium oxide and potassium hydroxide obtained in step (1) in a mass ratio of 1:2:2, placing the composite in a high-speed stirrer and rapidly stirring for 20 minutes to obtain a uniformly mixed composite;
[0078] (3) subjecting the composite to an extrusion molding process at an extrusion pressure of 10 MPa;
[0079] (4) The formed composite was placed in an activation furnace reactor, argon was introduced, and the heating rate was 5°C min -1 , reaction temperature 850℃, reaction time 1h;
[0080] (5) After the reaction product is cooled to room temperature, the reaction product is taken out, purified with 15 wt % dilute hydrochloric acid and washed with deionized water, dried in an oven at 120° C. for 12 h, and ball-milled for 2 h to obtain a capacitor carbon powder material.
[0081] When the reaction product is taken out in step (5), there is no mutual adhesion between the product and the reactor wall, and the mutual independence of the product and the reactor wall is relatively intact. The product is very easy to take out, indicating that there is no wall adhesion during the preparation process of capacitor carbon, further indicating that the method of the present invention can effectively eliminate the wall adhesion phenomenon during the preparation process of capacitor carbon.
[0082] This embodiment also provides a method for preparing a capacitor carbon electrode using the above capacitor carbon powder material, which comprises:
[0083] The capacitor carbon material, binder (LA133) and conductive additive (acetylene black) were dispersed in deionized water at a mass ratio of 8:1:1, and then the mixture was homogenized in a homogenizer. After homogenization for 5 hours, a capacitor carbon slurry was obtained.
[0084] The capacitor carbon slurry was evenly coated on a nickel foam with a thickness of 1 mm and a diameter of 12 mm, and placed in a constant temperature drying oven at 120° C. to remove the solvent, thereby obtaining a dry capacitor carbon electrode.
[0085] The concentration was 6 mol·L -1 The KOH solution and the concentration are 1 mol·L -1 TEABF4 solution was used as aqueous and organic electrolytes, and glass fiber filter membrane (GF / D, Whatman, GE) was used as the diaphragm. Electrode sheets of the same mass were assembled into supercapacitors, and subsequent capacitance performance evaluation was performed.
[0086] The specific surface area of the capacitor carbon material is 1820m 2 ·g -1 , the pore volume is 1.21cm 3 ·g -1 .
[0087] Figure 8 The cyclic voltammetry curve of the capacitor carbon electrode in the aqueous electrolyte system shows a good rectangular shape, indicating that it has excellent double-layer storage properties. -1 At a current density of 1.5 Å, the capacitance of the capacitive carbon electrode in an aqueous electrolyte system is as high as 235 F·g -1 At 1A·g -1 At a current density of 1.34 W / m, the capacitance of the capacitive carbon electrode in an organic electrolyte system is as high as 218 F·g -1 .
[0088] Example 3
[0089] This embodiment provides a method for preparing heavy oil-based capacitor carbon, wherein the preparation method comprises the following specific steps:
[0090] (1) crushing petroleum coke and passing it through a 200-mesh sieve to obtain petroleum coke powder;
[0091] (2) mixing the petroleum coke powder, magnesium sulfate and potassium hydroxide obtained in step (1) in a mass ratio of 1:3:1, placing the composite in a high-speed stirrer and rapidly stirring for 20 minutes to obtain a uniformly mixed composite;
[0092] (3) subjecting the composite to an extrusion molding process at an extrusion pressure of 10 MPa;
[0093] (4) The formed composite was placed in an activation furnace reactor, argon was introduced, and the heating rate was 5°C min -1 , reaction temperature 900℃, reaction time 1h;
[0094] (5) After the reaction product is cooled to room temperature, the reaction product is taken out, purified with 15 wt % dilute hydrochloric acid and washed with deionized water, dried in an oven at 120° C. for 12 h, and ball-milled for 2 h to obtain a capacitor carbon powder material.
[0095] When the reaction product is taken out in step (5), there is no mutual adhesion between the product and the reactor wall, and the mutual independence of the product and the reactor wall is relatively intact. The product is very easy to take out, indicating that there is no wall adhesion during the preparation process of capacitor carbon, further indicating that the method of the present invention can effectively eliminate the wall adhesion phenomenon during the preparation process of capacitor carbon.
[0096] This embodiment also provides a method for preparing a capacitor carbon electrode using the above capacitor carbon powder material, which comprises:
[0097] The capacitor carbon material, binder (LA133) and conductive additive (acetylene black) were dispersed in deionized water at a mass ratio of 8:1:1, and then the mixture was homogenized in a homogenizer. After homogenization for 5 hours, a capacitor carbon slurry was obtained.
[0098] The capacitor carbon slurry was evenly coated on a nickel foam with a thickness of 1 mm and a diameter of 12 mm, and placed in a constant temperature drying oven at 120° C. to remove the solvent, thereby obtaining a dry capacitor carbon electrode.
[0099] The concentration was 6 mol·L -1 The KOH solution and the concentration are 1 mol·L -1 TEABF4 solution was used as aqueous and organic electrolytes, and glass fiber filter membrane (GF / D, Whatman, GE) was used as the diaphragm. Electrode sheets of the same mass were assembled into supercapacitors, and subsequent capacitance performance evaluation was performed.
[0100] Fig. 9 is the pore distribution curve of the capacitor carbon material. The specific surface area of the capacitor carbon material is 2282m 2 ·g -1 , the pore volume is 1.24 cm 3 ·g -1 , the pore size distribution is concentrated between 0.5-100nm.
[0101] Fig.10 This is the X-ray powder diffraction spectrum of the capacitor carbon material.
[0102] Fig.11 This is the cycle performance diagram of the capacitor carbon electrode in the aqueous electrolyte system. After the electrode is cycled for 20,000 cycles, the capacity retention rate is as high as 99.9%, showing excellent cycle stability. After the capacitor carbon electrode is cycled for 20,000 cycles in the organic electrolyte system, the capacity retention rate is as high as 99.6%, also showing excellent cycle stability.
[0103] Example 4
[0104] This embodiment provides a method for preparing heavy oil-based capacitor carbon, wherein the preparation method comprises the following specific steps:
[0105] (1) crushing petroleum coke and passing it through a 200-mesh sieve to obtain petroleum coke powder;
[0106] (2) mixing the petroleum coke powder, calcium oxide and sodium hydroxide obtained in step (1) in a mass ratio of 1:3:1, placing the composite in a high-speed stirrer and rapidly stirring for 20 minutes to obtain a uniformly mixed composite;
[0107] (3) subjecting the composite to an extrusion molding process at an extrusion pressure of 10 MPa;
[0108] (4) The formed composite was placed in an activation furnace reactor, argon was introduced, and the heating rate was 5°C min -1 , reaction temperature 900℃, reaction time 1h;
[0109] (5) After the reaction product is cooled to room temperature, the reaction product is taken out, purified with 15 wt % dilute hydrochloric acid and washed with deionized water, dried in an oven at 120° C. for 12 h, and ball-milled for 2 h to obtain a capacitor carbon powder material.
[0110] When the reaction product is taken out in step (5), there is no mutual adhesion between the product and the reactor wall, and the mutual independence of the product and the reactor wall is relatively intact. The product is very easy to take out, indicating that there is no wall adhesion during the preparation process of capacitor carbon, further indicating that the method of the present invention can effectively eliminate the wall adhesion phenomenon during the preparation process of capacitor carbon.
[0111] This embodiment also provides a method for preparing a capacitor carbon electrode using the above capacitor carbon powder material, which comprises:
[0112] The capacitor carbon material, binder (LA133) and conductive additive (acetylene black) were dispersed in deionized water at a mass ratio of 8:1:1, and then the mixture was homogenized in a homogenizer. After homogenization for 5 hours, a capacitor carbon slurry was obtained.
[0113] The capacitor carbon slurry was evenly coated on a nickel foam with a thickness of 1 mm and a diameter of 12 mm, and placed in a constant temperature drying oven at 120° C. to remove the solvent, thereby obtaining a dry capacitor carbon electrode.
[0114] The concentration was 6 mol·L -1 The KOH solution and the concentration are 1 mol·L -1 TEABF4 solution was used as aqueous and organic electrolytes, and glass fiber filter membrane (GF / D, Whatman, GE) was used as the diaphragm. Electrode sheets of the same mass were assembled into supercapacitors, and subsequent capacitance performance evaluation was performed.
[0115] Fig.12is the pore distribution curve of the capacitor carbon material. The specific surface area of the capacitor carbon material is 2409m 2 ·g -1 , the pore volume is 1.29 cm 3 ·g -1 , the pore size distribution is concentrated between 0.5-100nm.
[0116] Fig.13 This is the X-ray powder diffraction spectrum of the capacitor carbon material.
[0117] Fig.14 The cyclic voltammetry curve of the capacitive carbon electrode in the aqueous electrolyte system shows a good rectangular shape, indicating that it has good double-layer storage properties. -1 At a current density of 1.37 W / m, the capacitance of the capacitive carbon electrode in an aqueous electrolyte system is as high as 238 F·g -1 At 1A·g -1 At a current density of 1.34 W / m, the capacitance of the capacitive carbon electrode in an organic electrolyte system is as high as 224 F·g -1 .
[0118] Example 5
[0119] This embodiment provides a method for preparing heavy oil-based capacitor carbon, wherein the preparation method comprises the following specific steps:
[0120] (1) crushing petroleum coke and passing it through a 200-mesh sieve to obtain petroleum coke powder;
[0121] (2) mixing the petroleum coke powder, calcium oxide and sodium hydroxide obtained in step (1) in a mass ratio of 1:3:1, placing the composite in a high-speed stirrer and rapidly stirring for 20 minutes to obtain a uniformly mixed composite;
[0122] (3) subjecting the composite to an extrusion molding process at an extrusion pressure of 10 MPa;
[0123] (4) The formed composite was placed in an activation furnace reactor, argon was introduced, and the heating rate was 5°C min -1 , reaction temperature 900℃, reaction time 1h;
[0124] (5) After the reaction product is cooled to room temperature, the reaction product is taken out, purified with 15 wt % dilute hydrochloric acid and washed with deionized water, dried in an oven at 120° C. for 12 h, and ball-milled for 2 h to obtain a capacitor carbon powder material.
[0125] When the reaction product is taken out in step (5), there is no mutual adhesion between the product and the reactor wall, and the mutual independence of the product and the reactor wall is relatively intact. The product is very easy to take out, indicating that there is no wall adhesion during the preparation process of capacitor carbon, further indicating that the method of the present invention can effectively eliminate the wall adhesion phenomenon during the preparation process of capacitor carbon.
[0126] This embodiment also provides a method for preparing a capacitor carbon electrode using the above capacitor carbon powder material, which comprises:
[0127] The capacitor carbon material, binder (LA133) and conductive additive (acetylene black) were dispersed in deionized water at a mass ratio of 8:1:1, and then the mixture was homogenized in a homogenizer. After homogenization for 5 hours, a capacitor carbon slurry was obtained.
[0128] The capacitor carbon slurry was evenly coated on a nickel foam with a thickness of 1 mm and a diameter of 12 mm, and placed in a constant temperature drying oven at 120° C. to remove the solvent, thereby obtaining a dry capacitor carbon electrode.
[0129] The concentration was 6 mol·L -1 The KOH solution and the concentration are 1 mol·L -1 TEABF4 solution was used as aqueous and organic electrolytes, and glass fiber filter membrane (GF / D, Whatman, GE) was used as the diaphragm. Electrode sheets of the same mass were assembled into supercapacitors, and subsequent capacitance performance evaluation was performed.
[0130] Fig.15 is the pore distribution curve of the capacitor carbon material. The specific surface area of the capacitor carbon material is 2212m 2 ·g -1 , pore volume is 1.15 cm 3 ·g -1 , the pore size distribution is concentrated between 0.5-100nm.
[0131] Fig.16 This is the X-ray powder diffraction spectrum of the capacitor carbon material.
[0132] Fig.17 The cyclic voltammetry curve of the capacitive carbon electrode in the aqueous electrolyte system shows a good rectangular shape, indicating that it has good double-layer storage properties. -1 At a current density of 1.5 Å, the capacitance of the capacitive carbon electrode in an aqueous electrolyte system is as high as 225 F·g -1 At 1A·g -1 At a current density of 2.5 Å, the capacitance of the capacitive carbon electrode in an organic electrolyte system is as high as 212 F·g -1 .
[0133] Example 6
[0134] This embodiment provides a method for preparing heavy oil-based capacitor carbon, wherein the preparation method comprises the following specific steps:
[0135] (1) mixing vacuum residue oil, calcium oxide and sodium hydroxide in a mass ratio of 1:2:2, placing the composite in a high-speed stirrer and rapidly stirring for 20 minutes to obtain a uniformly mixed composite;
[0136] (2) subjecting the composite to an extrusion molding process at an extrusion pressure of 10 MPa;
[0137] (3) The formed composite was placed in an activation furnace reactor, argon was introduced, and the heating rate was 5°C min -1 , reaction temperature 850℃, reaction time 1h;
[0138] (4) After the reaction product is cooled to room temperature, the reaction product is taken out, purified with 15 wt % dilute hydrochloric acid and washed with deionized water, dried in an oven at 120° C. for 12 h, and ball-milled for 2 h to obtain a capacitor carbon powder material.
[0139] When the reaction product is taken out in step (5), there is no mutual adhesion between the product and the reactor wall, and the mutual independence of the product and the reactor wall is relatively intact. The product is very easy to take out, indicating that there is no wall adhesion during the preparation process of capacitor carbon, further indicating that the method of the present invention can effectively eliminate the wall adhesion phenomenon during the preparation process of capacitor carbon.
[0140] This embodiment also provides a method for preparing a capacitor carbon electrode using the above capacitor carbon powder material, which comprises:
[0141] The capacitor carbon material, binder (LA133) and conductive additive (acetylene black) were dispersed in deionized water at a mass ratio of 8:1:1, and then the mixture was homogenized in a homogenizer. After homogenization for 5 hours, a capacitor carbon slurry was obtained.
[0142] The capacitor carbon slurry was evenly coated on a nickel foam with a thickness of 1 mm and a diameter of 12 mm, and placed in a constant temperature drying oven at 120° C. to remove the solvent, thereby obtaining a dry capacitor carbon electrode.
[0143] The concentration was 6 mol·L -1 The KOH solution and the concentration are 1 mol·L -1 TEABF4 solution was used as aqueous and organic electrolytes, and glass fiber filter membrane (GF / D, Whatman, GE) was used as the diaphragm. Electrode sheets of the same mass were assembled into supercapacitors, and subsequent capacitance performance evaluation was performed.
[0144] The specific surface area of the capacitor carbon material is 2325m2 ·g -1 , the pore volume is 1.52 cm 3 ·g -1 .
[0145] At 1A·g -1 At a current density of 2.5 Å, the capacitance of the carbon electrode in an aqueous electrolyte system is 255 F·g -1 At 1A·g -1 At a current density of 1.37 W / m, the capacitance of the capacitive carbon electrode in an organic electrolyte system is as high as 236 F·g -1 .
[0146] Example 7
[0147] This embodiment provides a method for preparing heavy oil-based capacitor carbon, wherein the preparation method comprises the following specific steps:
[0148] (1) mixing vacuum residue oil, calcium oxide and sodium hydroxide in a mass ratio of 1:3:1, placing the composite in a high-speed stirrer and rapidly stirring for 20 minutes to obtain a uniformly mixed composite;
[0149] (2) subjecting the composite to an extrusion molding process at an extrusion pressure of 10 MPa;
[0150] (3) The formed composite was placed in an activation furnace reactor, argon was introduced, and the heating rate was 5°C min -1 , reaction temperature 850℃, reaction time 1h;
[0151] (4) After the reaction product is cooled to room temperature, the reaction product is taken out, purified with 15 wt % dilute hydrochloric acid and washed with deionized water, dried in an oven at 120° C. for 12 h, and ball-milled for 2 h to obtain a capacitor carbon powder material.
[0152] When the reaction product is taken out in step (5), there is no mutual adhesion between the product and the reactor wall, and the mutual independence of the product and the reactor wall is relatively intact. The product is very easy to take out, indicating that there is no wall adhesion during the preparation process of capacitor carbon, further indicating that the method of the present invention can effectively eliminate the wall adhesion phenomenon during the preparation process of capacitor carbon.
[0153] This embodiment also provides a method for preparing a capacitor carbon electrode using the above capacitor carbon powder material, which comprises:
[0154] The capacitor carbon material, binder (LA133) and conductive additive (acetylene black) were dispersed in deionized water at a mass ratio of 8:1:1, and then the mixture was homogenized in a homogenizer. After homogenization for 5 hours, a capacitor carbon slurry was obtained.
[0155] The capacitor carbon slurry was evenly coated on a nickel foam with a thickness of 1 mm and a diameter of 12 mm, and placed in a constant temperature drying oven at 120° C. to remove the solvent, thereby obtaining a dry capacitor carbon electrode.
[0156] The concentration was 6 mol·L -1 The KOH solution and the concentration are 1 mol·L -1 TEABF4 solution was used as aqueous and organic electrolytes, and glass fiber filter membrane (GF / D, Whatman, GE) was used as the diaphragm. Electrode sheets of the same mass were assembled into supercapacitors, and subsequent capacitance performance evaluation was performed.
[0157] The specific surface area of the capacitor carbon material is 2320m 2 ·g -1 , the pore volume is 1.62 cm 3 ·g -1 .
[0158] At 1A·g -1 At a current density of 2.5 200 Å, the capacitance of the capacitive carbon electrode in an aqueous electrolyte system is 252 F·g -1 At 1A·g -1 At a current density of 1.5 Å, the capacitance of the capacitive carbon electrode in an organic electrolyte system is as high as 238 F·g -1 .
[0159] Example 8
[0160] This embodiment provides a method for preparing heavy oil-based capacitor carbon, wherein the preparation method comprises the following specific steps:
[0161] (1) mixing vacuum residue oil, calcium oxide and sodium hydroxide in a mass ratio of 1:4:1, placing the composite in a high-speed stirrer and rapidly stirring for 20 minutes to obtain a uniformly mixed composite;
[0162] (2) subjecting the composite to an extrusion molding process at an extrusion pressure of 10 MPa;
[0163] (3) The formed composite was placed in an activation furnace reactor, argon was introduced, and the heating rate was 5°C min -1 , reaction temperature 850℃, reaction time 1h;
[0164] (4) After the reaction product is cooled to room temperature, the reaction product is taken out, purified with 15 wt % dilute hydrochloric acid and washed with deionized water, dried in an oven at 120° C. for 12 h, and ball-milled for 2 h to obtain a capacitor carbon powder material.
[0165] When the reaction product is taken out in step (5), there is no mutual adhesion between the product and the reactor wall, and the mutual independence of the product and the reactor wall is relatively intact. The product is very easy to take out, indicating that there is no wall adhesion during the preparation process of capacitor carbon, further indicating that the method of the present invention can effectively eliminate the wall adhesion phenomenon during the preparation process of capacitor carbon.
[0166] This embodiment also provides a method for preparing a capacitor carbon electrode using the above capacitor carbon powder material, which comprises:
[0167] The capacitor carbon material, binder (LA133) and conductive additive (acetylene black) were dispersed in deionized water at a mass ratio of 8:1:1, and then the mixture was homogenized in a homogenizer. After homogenization for 5 hours, a capacitor carbon slurry was obtained.
[0168] The capacitor carbon slurry was evenly coated on a nickel foam with a thickness of 1 mm and a diameter of 12 mm, and placed in a constant temperature drying oven at 120° C. to remove the solvent, thereby obtaining a dry capacitor carbon electrode.
[0169] The concentration was 6 mol·L -1 The KOH solution and the concentration are 1 mol·L -1 TEABF4 solution was used as aqueous and organic electrolytes, and glass fiber filter membrane (GF / D, Whatman, GE) was used as the diaphragm. Electrode sheets of the same mass were assembled into supercapacitors, and subsequent capacitance performance evaluation was performed.
[0170] The capacitive carbon electrode has a high conductivity at 1A·g in an aqueous electrolyte system. -1 At a current density of 2.5, the capacitance of the carbon electrode is 260 F·g -1 After 10,000 cycles, the capacity retention rate of the electrode was as high as 99.8%, showing excellent cycle stability. -1 At a current density of 1.5 Å, the capacitance of the capacitive carbon electrode in an organic electrolyte system is as high as 245 F·g -1 After 10,000 cycles, the capacity retention rate is as high as 99.9%, showing excellent cycle stability.
[0171] Comparative Example:
[0172] This comparative example provides a method for preparing heavy oil-based capacitor carbon, wherein the preparation method comprises the following specific steps:
[0173] (1) crushing petroleum asphalt and passing it through a 200-mesh sieve to obtain petroleum asphalt powder;
[0174] (2) mixing the petroleum asphalt powder obtained in step (1) and potassium hydroxide in a mass ratio of 1:2, placing the composite in a high-speed stirrer and rapidly stirring for 20 minutes to obtain a uniformly mixed composite;
[0175] (3) subjecting the composite to an extrusion molding process at an extrusion pressure of 10 MPa;
[0176] (4) The formed composite was placed in an activation furnace reactor, argon was introduced, and the heating rate was 5°C min -1 , reaction temperature 850℃, reaction time 1h;
[0177] (5) After the reaction product was cooled to room temperature, the reaction product adhered tightly to the reactor wall, and it was difficult to remove the reaction product from the reactor. It was necessary to forcibly scrape the reaction product off with external force, indicating that a very serious wall adhesion problem occurred during the preparation of the capacitor carbon. The product was purified with 15wt% dilute hydrochloric acid and washed with deionized water, dried in an oven at 120°C for 12h, and ball-milled for 2h to obtain a capacitor carbon powder material.
[0178] (6) The capacitor carbon material, binder (LA133) and conductive additive (acetylene black) were dispersed in deionized water in a mass ratio of 8:1:1, and then the mixture was homogenized in a homogenizer. After homogenization for 5 hours, a capacitor carbon slurry was obtained.
[0179] (7) The capacitor carbon slurry is evenly coated on a nickel foam with a thickness of 1 mm and a diameter of 12 mm, and placed in a constant temperature drying oven at 120° C. to remove the solvent, thereby obtaining a dry capacitor carbon electrode.
[0180] (8) The concentration of 6 mol·L -1 The KOH solution and the concentration are 1 mol·L -1 TEABF4 solution was used as aqueous and organic electrolytes, and glass fiber filter membrane (GF / D, Whatman, GE) was used as the diaphragm. Electrode sheets of the same mass were assembled into supercapacitors, and subsequent capacitance performance evaluation was performed.
[0181] At 1A·g -1 At this current density, the capacity of the capacitive carbon electrode in an aqueous electrolyte system is only 120 F·g -1 .
[0182] At 1A·g -1 At this current density, the capacity of the capacitive carbon electrode in an organic electrolyte system is only 85 F·g -1 The capacity of the capacitor carbon material prepared in this comparative example in water and organic electrolyte systems is much lower than that in the embodiment.
Claims
1. A method for preparing a heavy oil-based high-capacitance capacitor carbon material, wherein: The method comprises: (1) mixing heavy oil, an oxygen-containing catalyst, and an activator to obtain a composite, and subjecting the composite to a molding process; wherein the mass ratio of the heavy oil to the oxygen-containing catalyst is 1:1-1:10, and the mass ratio of the heavy oil to the activator is 1:0.2-1:5; (2) activating the formed composite; (3) The activated product is acid-washed, washed with water until neutral, dried, and ball-milled to obtain the capacitor carbon material.
2. The preparation method according to claim 1, wherein The heavy oil includes one or a combination of two or more of petroleum coke, ethylene tar, heavy diesel, petroleum asphalt, vacuum residue oil, vacuum wax oil, atmospheric residue oil, and atmospheric wax oil.
3. The preparation method according to claim 1, wherein The oxygen-containing catalyst includes one or a combination of two or more of magnesium oxide, copper oxide, calcium oxide, aluminum oxide, magnesium sulfate, copper sulfate, iron sulfate, zinc sulfate, calcium sulfate, sodium carbonate, potassium carbonate, magnesium carbonate, copper carbonate, calcium carbonate, and zinc carbonate.
4. The preparation method according to claim 1, wherein The activator includes one or a combination of two or more of potassium hydroxide, sodium hydroxide, zinc chloride and phosphoric acid.
5. The preparation method according to claim 1, wherein The mass ratio of the heavy oil to the oxygen-containing catalyst is 1:1-1:
5.
6. The preparation method according to claim 1, wherein The mass ratio of the heavy oil to the activator is 1:0.5-1:5, preferably 1:0.5-1:
2.
7. The preparation method according to claim 1, wherein The molding process is performed by extrusion molding. Preferably, the pressure of the extrusion molding is 0.5-20 MPa.
8. The preparation method according to claim 1, wherein The activation reaction is carried out under protective gas conditions; preferably, the protective gas includes one or a combination of two or more of nitrogen, helium and argon.
9. The preparation method according to claim 8, wherein: The gas flow rate of the protective gas is 0.01-10L·min -1 .
10. The preparation method according to claim 1, wherein: The activation reaction temperature is 700-1000° C., and the reaction time is 0.5-3 h.
11. The preparation method according to claim 10, wherein: The heating rate during the activation reaction is 5-10°C·min -1 .
12. The preparation method according to claim 10, wherein: The particle size of the product obtained by ball milling is in the range of 0.1-50 μm, more preferably 10-30 μm.
13. Capacitor carbon material prepared by the method for preparing heavy oil-based high-capacitance capacitor carbon material according to any one of claims 1 to 12.
14. The capacitive carbon material according to claim 13, wherein: The specific surface area of the capacitor carbon material is 1000-3000m 2 ·g -1 , pore volume 0.05-5cm 3 ·g -1 , the pore size distribution is 0.5-100nm.
15. Use of the capacitive carbon material according to claim 13 or 14 as an electrode material for a supercapacitor.
16. A supercapacitor, wherein: The electrode material of the supercapacitor is made of the capacitive carbon material according to claim 13 or 14.